Docking studies of some pyrazole containing compounds in the cyclooxygenase-2 active site - Savić, Jelena; Anastasijević, Marija; Crevar, Milkica; Brborić, Jasmina (Archives of Pharmacy, 2023)
Whereas nonselective nonsteroidal anti-inflammatory drugs, such as aspirin, ibuprofen and diclofenac, inhibit both cyclooxygenase-1 and cyclooxigenase-2 enzymes, selective inhibitors target cyclooxygenase-2, which is overexpressed in inflammation, but also in cancer, atherosclerosis, Alzheimer’s disease, and Parkinson`s disease. Potential cardiovascular and hepatic side effects of cyclooxygenase-2 inhibitors have limited their use. The development of selective and safe cyclooxygenase-2 inhibitors remains a high priority in drug discovery. Based on the structure of previously investigated newly synthesized β-hydroxy-β-arylpropanoic acids, two groups of compounds were designed: analogs in which one of the benzene rings was replaced by a pyrazole, while the carboxyl group was retained, and amides of β-hydroxy-β-arylpropanoic acids with pyrazole. The compounds were docked into the 3D structure of the catalytic site of the enzyme cyclooxygenase-2 using AutoDock Vina 1.2.0. and the obtained interactions were compared with the interactions of celecoxib, a selective inhibitor. The amides had lower binding energies than the designed acids, which makes them attractive target compounds for synthesis and further examination.